Gastrodia and Uncaria (tianma gouteng) water extract exerts antioxidative and antiapoptotic effects against cerebral ischemia in vitro and in vivo. Issue 1 (December 2016) - Xian, Jia; Choi, Angus; Lau, Clara; Leung, Wing; Ng, Chun; Chan, Chun
Abstract Background Gastrodia and Uncaria decoction (tianma gouteng yin) is commonly used in Chinese medicine to treat cerebral ischemia. The aim of this study was to investigate the neuroprotective effects of a water extract (GUW) ofGastrodia elata (tianma; GE) andUncaria rhynchophylla (gouteng; UR) against ischemic insult using oxygen-glucose-deprived neuronal differentiated PC12 cells and rats subjected to middle cerebral artery occlusion (MCAO). Methods GUW was prepared by boiling raw GE and UR in water, followed by the lyophilization of the resulting extract. Neuronal differentiated PC12 cells were subjected to oxygen-glucose deprivation with or without GUW. The neuroprotective effects of GUW were compared with those of the corresponding GE and UR extracts to tease apart the effects of the different herbs. The synergistic effect of GE and UR in GUW was measured using a modified version of Burgi's formulae. The neuroprotective mechanisms viaNrf2 and anti-apoptotic pathways were investigated using real time PCR and enzyme activity assays. The neuroprotective effects of GUW were studied in vivo using a rat MCAO model. Neurofunctional outcome and brain infarct volume we assessed. H&E staining, cresyl violet staining and immunohistochemistry were performed to assess the histological outcome. Results The results of lactate dehydrogenase assay showed that GUW protected cells in a concentration-dependent manner (P  < 0.001). Moreover, the neuroprotective effects of GUW were greater than those of GE + UR (P  = 0.018). Burgi's formula showed that the herbs in GUW acted synergistically to protect cells from ischemic injury. GUW significantly upregulatedBcl -2 expression (P  = 0.0130) and reduced caspase-3 activity by 60 % (P  < 0.001). GUW upregulatedNrf -2 expression (P  = 0.0066) and the antioxidant response element pathway genes. The infarct volume was reduced by 55 % at day 7 of reperfusion (P  < 0.001), and significant improvements were observed in the neurological deficit score and beam-walking test at 7 days (P  < 0.001). H&E and cresyl violet staining revealed higher tissue integrity in the GUW treatment group compared with MCAO rats. Conclusion GUW modulated the antioxidant system and antiapoptotic genes in oxygen-glucose deprived neuronal differentiated PC12 cells and MCAO sprague–dawley rats.